2014
DOI: 10.1007/s11947-014-1363-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties of Ethylene Vinyl Alcohol/Epsilon-Polylysine Films and Their Application in Surimi Preservation

Abstract: 10 11Polymer films based on ethylene vinyl copolymers (EVOH) containing a 29% (EVOH29) and a 12 44% molar percentage of ethylene (EVOH44), and incorporating ε-polylysine (EPL) at 0, 1, 5 13 and 10% were successfully made by casting. The optical properties and the amount of EPL 14 released from the films to phosphate buffer at pH 7.5 were evaluated, films showing great 15 transparency and thoseEVOH29 copolymer releasing a greater amount of EPL. The 16 antimicrobial properties of the resulting films were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…HHP can inactivate L. monocytogenes by causing morphological changes in its internal and external cellular structures and through cell wall rupture and membrane damage (Huang and others ). Muriel‐Galet and others () observed that ε‐PL affected the membrane via electrostatic adsorption and caused cell collapse. In this study, SEM analysis revealed the characteristics underlying the efficient inactivation of L. monocytogenes by the combined treatment.…”
Section: Discussionmentioning
confidence: 99%
“…HHP can inactivate L. monocytogenes by causing morphological changes in its internal and external cellular structures and through cell wall rupture and membrane damage (Huang and others ). Muriel‐Galet and others () observed that ε‐PL affected the membrane via electrostatic adsorption and caused cell collapse. In this study, SEM analysis revealed the characteristics underlying the efficient inactivation of L. monocytogenes by the combined treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ε-PL is a naturally occurring nylon-like polymer showing antimicrobial activities, but is not a plastic-friendly polymer, because the addition of a large amount of ε-PL to plastics induced a phase separation or color change even in hydrophilic plastics. , As mentioned earlier, the PL n + /BEHS – -complex is soluble in organic solvents. This chemical property would enable the complex to be miscible in commodity hydrophobic plastics such as PP.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the main directions for research on microbial control in surimi products include thermal sterilization, chemical bacteriostasis, and physical bacteriostasis . The combination of various methods such as basic amino acids coupled with microwave irradiation can also be used to achieve better antibacterial effects.…”
Section: Introductionmentioning
confidence: 99%